ANALISIS TUTURAN PENOLAKAN DALAM DISKUSI KELAS - Muzakkar Muzakkar; Sultan Sultan; Andi Agussalim AJ (Universitas Negeri Makassar, 2020)
Analysis of Speech Rejection in Class Discussion. This study was designed to describe agreement, strategy and agreement. Researchers use qualitative research types with descriptive designs. Data collection was carried out using a competent, free listening technique. Data analysis through interpretation. The results showed that the form of explanation consisted of declarative speech, interrogative speech and imperative speech. Furthermore, the payment strategy consists of regrets, hopes, alternative approvals, future or past receipts, attempts to accept, receipts made as demands and avoidance. The questions asked consist of criticizing, refuting, refuting, seeking the truth, refuting and refuting criticism.